Nitrile Imines as Peptide and Oligonucleotide Photo-Cross-Linkers in Gas-Phase Ions - Wan, Jiahao; Nytka, Marianna; Qian, Haocheng; Vu, Kim; Lemr, Karel; Tureček, František (Journal of the American Society for Mass Spectrometry, 2024)
Nitrile imines produced by photodissociation of 2,5-diaryltetrazoles undergo cross-linking reactions with amide groups in peptide-tetrazole (tet-peptide) conjugates and a tet-peptide-dinucleotide complex. Tetrazole photodissociation in gas-phase ions is efficient, achieving ca. 50% conversion with 2 laser pulses at 250 nm. The formation of cross-links was detected by CID-MS3 that showed structure-significant dissociations by loss of side-chain groups and internal peptide segments. The structure and composition of cross-linking products were established by a combination of UV-vis action spectroscopy and cyclic ion mobility mass spectrometry (c-IMS). The experimental absorption bands were found to match the bands calculated for vibronic absorption spectra of nitrile imines and cross-linked hydrazone isomers. The calculated collision cross sections (CCSth) for these ions were related to the matching experimental CCSexp from multipass c-IMS measurements. Loss of N2 from tet-peptide conjugates was calculated to be a mildly endothermic reaction with ΔH0 = 80 kJ mol-1 in the gas phase. The excess energy in the photolytically formed nitrile imine is thought to drive endothermic proton transfer, followed by exothermic cyclization to a sterically accessible peptide amide group. The exothermic nitrile imine reaction with peptide amides is promoted by proton transfer and may involve an initial [3 + 2] cycloaddition followed by cleavage of the oxadiazole intermediate. Nucleophilic groups, such as cysteine thiol, did not compete with the amide cyclization. Nitrile imine cross-linking to 2'-deoxycytidylguanosine was found to be >80% efficient and highly specific in targeting guanine. The further potential for exploring nitrile-imine cross-linking for biomolecular structure analysis is discussed.
Keywords: nitrily; protony; oligonukleotidy; Protons; iminy; Peptides; Oligonucleotides; Ions; ionty; Imines; Nitriles; peptidy; Amides; amidy; tetrazoly; Tetrazoles